(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
In this article, the history, development, stages of development of the Uzbek national dance art, specific features of our dance schools and regional national costumes, as well as the wide-scale work on the development of the art of dance. , the artistic features of dance schools are described.